Self-Disinfecting Paints with the Natural Antimicrobial Substances: Colophony and Curcumin - Querido, Micaela Machado (2021)
The risk of infection arising from indirect sources-namely, contaminated surfaces-has been proved, particularly in healthcare facilities. In the attempt to minimize this problem, innumerable research projects involving the development of surfaces with self-disinfecting properties are being conducted. In this work, wall-paints with self-disinfecting properties were developed with the scope of being applied in environments prone to contamination, such as those at healthcare settings. Our approach was to develop new paint formulations containing two natural plant-based products with known antimicrobial activity-colophony (CLF) and curcumin (CUR). The natural substances were separately incorporated on a commercial paint and their antibacterial activity was evaluated with several bacterial species following ISO 22196. To assess the paints' safety, cytotoxicity tests were performed on HaCaT and A549 cell lines, using tests on extracts and direct contact tests, as suggested by the standardized protocol ISO 10993. In general, both paints containing CLF and CUR were able to reduce the bacterial growth after 24 h, compared with the control, the commercial unmodified paint. Colophony was even able to reduce the number of culturable bacteria by over 2 log for Staphylococcus aureus, Escherichia coli, and Bacillus cereus. Regarding the cytotoxicity tests performed (WST-1, NRU, and LDH), both formulations revealed promising results regardless of the methodology used.